From Inactive to Inaccessible: Legal Protection of Dormant Accounts in the Banking System - Muhammad Dzakwan Dzaputra; Mohammad Arif; Tri Abriana Ma'ruf (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
Penelitian ini merupakan penelitian hukun normatif dengan pendekatan perundang-undangan dan konseptual. Bahan hukum yang digunakan terdiri atas bahan hukum primer, sekunder, dan tersier yang dianalisis secara preskriptif untuk menjelaskan ketentuan hukum yang berlaku serta memberikan argumentasi dan rekomendasi normatif. Hasil penelitian menunjukkan pengaturan pemblokiran rekening nasabah di Indonesia belum dirumuskan secara eksplisit dan komprehensif dalam satu ketentuan khusus, melainkan tersebar dalam berbagai ketentuan yang bersifat umum, terutama terkait prinsip kehati-hatian dan rezim pencegahan tindak pidana keuangan. Absennya pengaturan yang secara jelas mengatur kewajiban, prosedur, dan batas waktu pemblokiran menyebabkan perlindungan hukum preventif terhadap nasabah menjadi lemah dan berpotensi menimbulkan ketidakpastian bagi nasabah dalam mengakses dananya. Perlindungan hukum setelah pemblokiran pada dasarnya bersifat represif, melalui mekanisme pengaduan, reaktivasi rekening, dan upaya hukum perdata. Namun tanpa fondasi preventif yang jelas dan tegas, perlindungan represif tersebut belum sepenuhnya menjamin kepastian hukum dan keseimbangan kedudukan antara bank dan nasabah. Rekomendasi penelitian ini menekankan perlunya Otoritas Jasa Keuangan meningkatkan efektivitas penerapan POJK Nomor 24 Tahun 2025 tentang Pengelolaan Rekening pada Bank Umum, khususnya terkait kewajiban pemberitahuan, standar rekening dormant, dan prosedur reaktivasi rekening, serta mendorong perbankan untuk menerapkan kebijakan pemblokiran dengan tetap menjunjung prinsip kehati-hatian, transparansi, dan perlindungan konsumen. Abstract: This study aims to examine and analyze the legal regulations governing the blocking of customer accounts by banks, as well as the forms of legal protection provided for dormant customer accounts after they have been blocked by banks. This research is normative legal research with a legislative and conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed prescriptively to explain the applicable legal provisions and provide normative arguments and recommendations. The results of the study show that the regulation of customer account blocking in Indonesia has not been explicitly and comprehensively formulated in a specific provision, but is scattered in various general provisions, especially those related to the principle of prudence and the regime for the prevention of financial crimes. The absence of regulations that clearly stipulate the obligations, procedures, and time limits for blocking accounts has resulted in weak preventive legal protection for customers and has the potential to cause uncertainty for customers in accessing their funds. Legal protection after blocking is essentially repressive, through complaint mechanisms, account reactivation, and civil law efforts. However, without a clear and firm preventive foundation, such repressive protection does not fully guarantee legal certainty and balance between banks and customers. This research recommendation emphasizes the need for the Financial Services Authority to improve the effectiveness of the implementation of POJK Number 24 of 2025 concerning Account Management at Commercial Banks, particularly in relation to notification obligations, dormant account standards, and account reactivation procedures, as well as encouraging banks to implement blocking policies while upholding the principles of prudence, transparency, and consumer protection